Optimal Management of Evolving Hierarchies - Hougaard Jens Leth; Moreno-Ternero Juan D.; Østerdal Lars Peter (Copenhagen Business School (CBS), Department of Economics, 2018)
We study the optimal management of evolving hierarchies, which abound in real-life phenomena. An initiator invests into finding a subordinate, who will bring revenues to the joint venture and who will invest herself into finding another subordinate, and so on. The higher the individual investment (which is private information), the higher the probability of finding a subordinate. A transfer scheme specifies how revenues are reallocated, via upward transfers, as the hierarchy evolves. Each transfer scheme induces a game in which agents decide their investment choices. We consider two optimality notions for schemes: initiator-optimal and socially-optimal schemes. We show that the former are schemes imposing to each member a full transfer to two recipients (the predecessor and the initiator) with a constant ratio among the transfers. We show that the latter are schemes imposing full transfers to the immediate predecessors.
hdl:10398/9701
Keywords: C70; L24; M52; 330; Optimal transfer schemes; Hierarchies; Management; Nash equilibrium